Implementation of Nigeria's surgical plan: leveraging media engagement for cleft lip and palate to drive advocacy for access to surgical healthcare - Justina O. Seyi-Olajide; Oti N. Aria; Nkeiruka (Nk); Paul Lobi; Emmanuel A. Ameh (Inishmore Laser Scientific Publishing Ltd, 2024)
# Background Global health advocacy plays a crucial role in addressing emerging health challenges, including the provision of surgical healthcare care in low- and middle-income countries (LMICs). Nigeria launched its national surgical, obstetrics, anaesthesia, and nursing plan (NSOANP) in 2019 to improve access to surgical services, including cleft lip and palate. This report examines the potential of media engagement as a catalyst for advocacy initiatives to strengthen surgical systems. # Methods The study conducted media and advocacy workshops targeting journalists from various media outlets across Nigeria. Workshops included didactic lectures, presentations, role plays, and group discussions. Participants were evaluated through pre- and post-tests. Follow-up activities tracked participants' reporting and awarded prizes for outstanding reporting on cleft and surgical care. # Results One hundred and three journalists, including 61 (59.2%) males and 42 (39.8%) females participated, showing significant improvement in knowledge about cleft lip and palate anomalies and access to surgical care (p = 0.03). Post-workshop outputs included public enlightenment programmes, radio dramas, and published reports. The initiative awarded prizes to 9 journalists for quality reporting. # Conclusions Media engagement is a potent tool for advocating for surgical care access. The success of this initiative underscores the importance of collaboration between stakeholders and the need for sustained efforts to support advocacy for access to surgical healthcare.